EFL LEARNERS’ READING LEARNING IN WEB BASED INSTRUCTION SETTING - Yusup Supriyono (Universitas Islam Sultan Agung, 2018)
This research is aimed at exploring reading learning performed by English foreign language learners when Web based instruction is integrated into reading classroom. Teaching learning activity follows the steps: orientation, discussion, material exploration, action, test, and reflection. Two data collecting methods—journal and interview are administered to three students of the fourth semester of English Department in University of Siliwangi Tasikmalaya Indonesia after the selected individuals finished the reading course for one semester. The findings show that the teaching-learning process using Web based instruction enlarges the students’ reading activity, enhances micro and macro reading competences, and builds affection.